Control of an induction motor using sliding mode linearization - Etien, Eric; Cauet, Sébastien; Rambault, Laurent; Champenois, Gérard (Zielona Góra: Uniwersytet Zielonogórski)
Nonlinear control of the squirrel induction motor is designed using sliding mode theory. The developed approach leads to the design of a sliding mode controller in order to linearize the behaviour of an induction motor.
Keywords: induction motor; sliding mode control; linearization